2004
DOI: 10.1063/1.1805731
|View full text |Cite
|
Sign up to set email alerts
|

La 0.8 Sr 0.2 MnO 3 -heterostructure effects on the dielectric properties of PbTiO3-based thin films

Abstract: Articles you may be interested inAnalysis of diffuse phase transition and relaxorlike behaviors in Pb 0.5 Sr 0.5 Ti O 3 films through dc electric-field dependence of dielectric response Appl. Phys. Lett. 90, 242908 (2007); 10.1063/1.2748080Self-poled Pb ( Zr , Ti ) O 3 films with improved pyroelectric properties via the use of ( La 0.8 Sr 0.2 ) MnO 3 /metal substrate heterostructuresThe present paper deals with substrate heterostructure effects on the microstructure and dielectric properties of Sm, Er, and La … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…In the wet chemical process, the preparation of high-quality films depends strongly on the synthesis of an appropriate precursor, the coating, the crystallization conditions and the substrate used. There are numerous reports on the preparation of LSMO films by the wet chemical process using different precursor solutions on various substrates such as Si, SiO 2 /Si, Al 2 O 3 , Pt/Si, SrTiO 3 and Y-stabilized zirconia [7,[13][14][15][16][17]. However, it is also important to understand the relationships of the growth conditions with the microstructures and electrical properties of the LSMO films fabricated by the wet chemical process.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the wet chemical process, the preparation of high-quality films depends strongly on the synthesis of an appropriate precursor, the coating, the crystallization conditions and the substrate used. There are numerous reports on the preparation of LSMO films by the wet chemical process using different precursor solutions on various substrates such as Si, SiO 2 /Si, Al 2 O 3 , Pt/Si, SrTiO 3 and Y-stabilized zirconia [7,[13][14][15][16][17]. However, it is also important to understand the relationships of the growth conditions with the microstructures and electrical properties of the LSMO films fabricated by the wet chemical process.…”
Section: Introductionmentioning
confidence: 98%
“…Grishin et al [6] reported that it is possible to grow epitaxial heterostructures of Pb(Zr, Ti)O 3 /LSMO onto LaAlO 3 (1 0 0) single crystal. Es-Souni et al [7] showed that the use of LSMO as bottom electrode for lead titanatebased films affects strongly their chemistry and consequently their properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15͒ and PbTiO 3 / ͑La, Sr͒MnO 3 structures. 16 As a result, the formation of such an interdiffusive layer may have great influence on the electrical properties of BST/LSMO heterostructure. Furthermore, to analyze the crystallization and epitaxial behavior, a pattern of selected area electron diffraction ͑SAED͒ was taken from the area covering the interface of BST and LSMO films.…”
Section: Resultsmentioning
confidence: 99%
“…LSMO is also a metallic oxide with a resistivity at room temperature of approximately 10 À5 O m [6]. Recently, LSMO films have attracted great interest, because of their potential to be used as a bottom electrode in the fabrication of ferroelectrics memories and integrated ferroelectric microelectro-mechanical system devices [7][8][9]. LSMO shows great potential to be used as a bottom electrode layer because of the following reasons.…”
Section: Introductionmentioning
confidence: 99%